Many ways : how families practice their beliefs and religions - Rotner, Shelley; Kelly, Sheila M. (Minneapolis, Minn. : Millbrook Press, 2006)
Photographs show the differences and similarities in the ways people practice their beliefs.
Includes bibliographical references (p. [32]).
Keywords: Religions -- Pictorial works -- Juvenile literature; Religions